Ambient particulate matter and carbon monoxide at an urban site of India: Influence of anthropogenic emissions and dust storms. (June 2017) - Yadav, Ravi; Sahu, L.K.; Beig, G.; Tripathi, Nidhi; Jaaffrey, S.N.A.
Abstract: Continuous measurements of PM2.5, PM10 and CO were conducted at an urban site of Udaipur in India from April 2011 to March 2012. The annual mean concentrations of PM2.5, PM10 and CO were 42 ± 17 μg m −3, 114 ± 31 μg m −3 and 343 ± 136 ppbv, respectively. Concentrations of both particulate and CO showed high values during winter/pre-monsoon (dry) period and lowest in the monsoon season (wet). Local anthropogenic emission and long-range transport from open biomass burning sources along with favourable synoptic meteorology led to elevated levels of pollutants in the dry season. However, higher values of PM10 /PM2.5 ratio during pre-monsoon season were caused by the episodes of dust storm. In the monsoon season, flow of cleaner air, rainfall and negligible emissions from biomass burning resulted in the lowest levels of pollutants. The concentrations of PM2.5, PM10 and CO showed highest values during morning and evening rush hours, while lowest in the afternoon hours. In winter season, reductions of PM2.5, CO and PM10 during weekends were highest of 15%, 13% and 9%, respectively. In each season, the highest PM2.5 /PM10 ratio coincided with the highest concentrations of pollutants (CO and NOX ) indicating predominant emissions from anthropogenic sources. Exceptionally high concentrations of PM10 during the episode of dust storm were due to transport from the Arabian Peninsula and Thar Desert. Up to ∼32% enhancements of PM10 were observed during strong dust storms. Relatively low levels of O3 and NOx during the storm periods indicate the role of heterogeneous removal. Graphical abstract: This Image indicates dust plumes over western region of India. Image Courtesy: Aqua-MODIS (NASA) on 20 March 2012. Highlights: Time resolved measurements of PM2.5, PM10 and CO at an urban site in western India. Seasonality of PMs and CO due to seasonal change in emission and transport. Meteorology dominates over emissions during monsoon in PMs and CO distribution. Contributions of windblown dust to PM10 and incomplete combustion to CO and PM2.5. About 32% increase of PM10 during the dust storms in pre-monsoon season.